Synthesis, Characterization and Investigation Liquid Crystalline, Properties of 1, 2, 3-triazole Derivatives via Cycloaddition Reaction - Nisreen H Karam (Journal of Global Pharma Technology, 2018)
The new of compounds synthesized by sequence reactions starting from a reaction of 3-phenylenediamine  or 4-phenylenediamine  with chloroacetyl chloride to produce the compounds [I]a,b, then the compounds[I]a,b reacted with sodium azide to yield compounds[II]a,b that reacted 1,3-dipolarcycloaddition reaction  with   acrylic acid to give compounds [III]a,b these compounds reacted with  methanol led to ester compounds[IV]a,b then reacted with  hydrazine to give acid hydrazide [V]a,b . Finally compounds [V]a,b reacted with   aromatic aldehydes to product shiff bases derivatives. The compounds characterized by mp. , IR, 1HNMR in addition to mass spectroscopy for some of them the liquid crystals properties were studied by using polarized optical microscope (pom) and deferential calorimetry (DSC).    Keywords: Liquid crystal, 1, 2, 3-triazole ring, Clicks reaction.